The Dance of Empathy and Understanding: Nurturing Rapport in the Counselor-Client Connection - Ramadhani, Lusi; Karneli, Yeni; Hariko, Rezki (Jurnal Bimbingan dan Konseling Terapan, 2024)
This article explores the analysis of individual counseling service strategies in relation to the counselor-client relationship. The research method employed in this study is a literature review analysis. The results reveal that counseling is a process of providing assistance through counseling interviews conducted by a professional counselor to individuals facing various problems. Individual counseling emerges as a core service within guidance and counseling, enabling clients to express their personal issues and find solutions. The counselor-client relationship is of utmost importance, requiring the counselor to establish rapport, trust, and effective communication with the client. Building a strong therapeutic alliance is crucial for successful counseling outcomes. The counselor-client relationship is dynamic and evolves over time, fostering trust, mutual understanding, and personal growth. Furthermore, maintaining appropriate boundaries and adhering to ethical standards are vital aspects of the counseling relationship.